Integrated management systems building technique: inspection and repair of non-structural elements - Ferraz, G. T.; De Brito, J.; De Freitas, V. P.; Silvestre, J. D. (Revista ALCONPAT, 2015)
The international scientific community has devoted a great deal of attention to the vast area of knowledge of inspection, diagnosis, maintenance and renovation of buildings, which may be used in the development of integrated building management systems. In this article, we provide a framework for the evaluation methods of the pathology of non-structural elements of buildings, based on current methods, presenting some of the challenges in this area. We present a model to be enforced in the integrated management systems of a building, along with some of the challenges of this area. We also introduce a model to be enforced in the integrated management systems of a building, forming a conductor line and a consistent foundation for a system to be put in place. Keywords: construction pathology; expert system based on performance; evaluation method; building management